The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Native Regiella Endosymbionts Provide Strong Parasitoid Protection With Limited Impacts on Fitness and Virus Transmission in Myzus persicae - Qiong Yang; Perran A. Ross; Alex Gill; Xinyue Gu; Neha Durugkar; Jia Chang; Owen J. Holland; Paul A. Umina; Christoph Vorburger; Torsten N. Kristensen; Ary A. Hoffmann (Environmental Microbiology, 2026)
A substantial literature has developed on facultative endosymbionts of insects, often portrayed as having large effects on their hosts, ranging from mutualistic to parasitic. The aphid endosymbiont Regiella insecticola occurs naturally in Myzus persicae and has potential biocontrol applications. Here, we examined the effects of native Regiella in two clones of M. persicae from Australia collected two decades apart, to assess whether these effects could explain the persistence of Regiella in natural populations. Genome sequencing revealed > 99.99% similarity between the Regiella strains from these clones. Regiella was stable in laboratory cultures and transmitted horizontally on excised leaves and intact plants. Fitness assays showed Regiella had modest costs to aphid reproduction but provided some benefits under heat stress, with no host‐plant‐specific effects. Regiella did not impact transmission of turnip yellows virus. Regiella provided strong protection against parasitism by two common parasitoid wasps, Diaeretiella rapae and Aphidius colemani . These findings indicate that while Regiella has limited fitness effects on M. persicae in the absence of parasitoids, its strong protection against parasitism underscores an important ecological function. However, these effects alone are not sufficient to explain the low incidence of Regiella in natural M. persicae populations, despite evidence for horizontal transfer.

Calibration of the species threat abatement and restoration metric's threat abatement component in a Costa Rican landscape - Louise Mair; Thomas M. Brooks; Randall R. Jimenez; Nicholas B. W. Macfarlance; Tony Nello; Antonin Vergez; Leon Bennun; Florence Curet; Annie Dakmejian; Edward Ellis; Melibea Gallo; Philip J. K. McGowan; et al. (Conservation Biology, 2026)
Achieving global conservation policy goals requires the ability to set and measure progress toward science‐based targets for biodiversity. The species threat abatement and restoration (STAR) metric was developed to enable actors to set science‐based targets for species. STAR scores quantify the potential contribution of actions to abate threats and restore habitat to reduce species extinction risk in a particular place and can be aggregated and disaggregated among species, threats, and areas of interest. Estimated STAR scores are based on data from the International Union for Conservation of Nature Red List and provide initial information on the species and threats expected to be present in an area. Operationalization of the metric requires verification of the presence of species and the presence and severity of threats in the area to inform calculation of a calibration STAR score. We applied a pilot calibration process for the threat abatement component of STAR (STAR T ) in the San Jose northern subcatchments landscape in Costa Rica. We used specialist knowledge and geospatial analyses of habitat loss to determine the species present and the intensity of threats affecting them in the landscape. Calibration yielded a more even distribution of scores among threats than was apparent from estimated STAR T and identified that reducing the threat from livestock farming and ranching had the greatest potential to reduce species extirpation risk. Calibration also showed that there is an opportunity to prevent the extinction of a critically endangered endemic amphibian, but the species’ presence requires confirmation. The pilot demonstrated how specialist knowledge and geospatial analyses can be combined during calibration to produce a calibrated STAR T score capable of informing science‐based targets for species conservation. Our calibration process can be applied to other areas.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Advancements in weed mapping: A systematic review - Mohammad Jahanbakht; Alex Olsen; Ross Marchant; Emilie Fillols; Mostafa Rahimi Azghadi (European Journal of Agronomy, 2026)

Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Morphological and physiological response of conifer seedlings to drought conditioning - Anna C. Ross; Jeremiah R. Pinto; Justin S. Crotteau; Alex Goke; Cara R. Nelson; David L. R. Affleck; Andrew J. Larson (New Forests, 2025)

Measuring Fluxes of Nitrous Oxide ( N 2 O ) From an Intensively Farmed Wasted Peatland Field in the UK Using the Eddy Covariance Method - Nicholas Cowan; Alex Cumming; Ross Morrison; Hannah Clilverd; Luke Palmer; Chris D. Evans (Global Change Biology, 2025)
While the number of studies quantifying emissions of the greenhouse gases (GHGs) carbon dioxide (CO 2 ) and methane (CH 4 ) from peatland farming has increased in recent years, high uncertainty regarding the magnitude and drivers of emissions of the powerful GHG nitrous oxide (N 2 O) from farmed peatland soils remains. This study used eddy covariance to measure fluxes of N 2 O over a 3‐year period from a commercial farm in the East Anglian Fens, in a rotationally cropped field with a 56 cm surface layer of peaty soil. Over the 41‐month measurement period, the average (±95% CI) monthly field‐scale emission was 0.50 ± 0.17 kg N 2 O‐N ha −1 , which equates to approximately 6.0 ± 2.0 kg N 2 O‐N ha −1 year −1 . Emissions of N 2 O at the field site were controlled by thresholds in both soil temperature (low fluxes below ~12°C) and volumetric water content (low fluxes below ~65%). Where these thresholds were simultaneously exceeded at any depth within the top metre of the soil profile, N 2 O emissions increased by an order of magnitude. Higher water level management in the summer months resulted in a significant increase in annual N 2 O emissions, estimated to be up to 10 kg N 2 O‐N ha −1 year −1 higher than in years when the water table was lower. Elevated emissions of N 2 O were largely controlled by environmental conditions (i.e., moisture and temperature). These conditions were in turn influenced by crop management, with higher emissions occurring when the field was cultivated for potatoes (compared to wheat and beans) which we attribute to a combination of higher water level management, overhead irrigation, relatively low crop nitrogen demand and solar heating of the exposed soil surface.

Conservation planning for environmental water to climate refugia in the manageable Murray–Darling Basin - Joanne M. Bennett; Simon Linke; Shane Brooks; Alex Bush; James Hitchcock; Carmel Pollino; Ross M. Thompson (Journal of Environmental Management, 2025)

Endosymbionts impact ladybird predation rates of aphids in a temperature-dependent manner - Katrine Bitsch; Perran A. Ross; Alex Gill; Qiong Yang; Monica Stelmach; Ashley G. Callahan; Michael Ørsted; Ary A. Hoffmann; Torsten N. Kristensen (BioControl, 2025)
Aphids are pests that cause major economic losses to growers on a global scale. Current management strategies rely heavily on pesticides, but some effective pesticides are being withdrawn, and the efficiency of remaining pesticides is decreasing, as aphids build up resistance. Biological control using predators can provide an important sustainable alternative to pesticides under some circumstances, and the deliberate introduction of facultative bacterial endosymbionts that induce host fitness costs and reduce plant virus transmission has been suggested as another strategy to combat aphid damage. However, new control options should not be antagonistic, and there might be a concern that the effectiveness of biocontrol can be altered/reduced by endosymbiont presence in hosts. We therefore tested if predation by two ladybirds, Adalia bipunctata and Harmonia conformis , on green peach aphid, Myzus persicae, and oat aphid, Rhopalosiphum padi , was affected by transinfected Rickettsiella viridis and Regiella insecticola endosymbionts and we used different temperatures to assess if any effects depended on temperature. The predation rate (defined as the time it takes for ladybirds to capture and eat the aphids) of aphids infected by either endosymbiont was higher at 14 °C compared to the rate at which uninfected aphids of both species were eaten. The opposite pattern was seen for both aphid species at 20 °C and for one host-endosymbiont combination at 26 °C. Aphids were eaten faster at 26 °C compared to at the lower temperatures, while differences in predation rates between 14 °C and 20 °C depended on species. Another important outcome of our study was that transmission of endosymbionts from aphids to ladybirds did not occur. Our findings reveal a highly temperature-dependent effect of the investigated endosymbionts on ladybird predation rates on aphids. The temperature dependence of endosymbiont-predation interactions suggests that seasonal climatic variation should be considered when assessing the impact of endosymbionts in settings where biological control is important.

A tool to support food substance safety evaluations in the United States - Christine M. Crincoli; Jennifer L.G. van de Ligt; Alex K. Eapen; Anthony T. Pavel; Paul R. Hanlon; Kelly Almond-Abbate; Esther Haugabrooks; Jason Hlywka; Vivian Lu; Fleur de Mooij; Margaret Pandis; Ross Peterson; et al. (Regulatory Toxicology and Pharmacology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Deleterious effects of the endosymbiont Rickettsiella viridis in Myzus persicae are environmentally dependent - Perran A. Ross; Michail C. Tyrilos; Neha Durugkar; Alex Gill; Nadieh de Jonge; Qiong Yang; Xinyue Gu; Ary A. Hoffmann; Torsten N. Kristensen (Journal of Pest Science, 2025)
Endosymbionts living within insect cells can modify host fitness and could provide new tools for pest control. The endosymbiont Rickettsiella viridis has been transferred experimentally into the green peach aphid, Myzus persicae, a globally important agricultural pest. This Rickettsiella spreads via vertical and horizontal transmission and induces host fitness costs which could potentially suppress pest populations. Endosymbiont prevalence can fluctuate in natural populations, and it is important to identify factors that contribute to their spread or loss. Here, we explore the effects of Rickettsiella infection when aphids are reared on eight different host plants or exposed to thermal, starvation and desiccation stresses. Rickettsiella infection reduced M. persicae fecundity and longevity across all host plants, but the magnitude of costs varied among host plants and generations. Rickettsiella was horizontally transmitted and spread in caged populations at initial ratios of 1:2 Rickettsiella (+): Rickettsiella (−) on all host plants, but with limited long-term persistence under cycling 20–30 °C. We also identified temperature-dependent costs of Rickettsiella infection on heat knockdown time, chill coma recovery, and starvation tolerance. Finally, we present evidence that Rickettsiella infection reduces host activity levels under heat stress. Our results suggest that Rickettsiella infections induce a variety of deleterious effects but with complex environment-dependent interactions. This work helps understand ecological conditions that enhance or limit the spread of these endosymbionts in aphid populations.

Ocean Gliders for Planning and Monitoring Remote Canadian Pacific Marine Protected Areas - Tetjana Ross; Hayley Dosser; Jody Klymak; Wiley Evans; Alex Hare; Jennifer Jackson; Stephanie Waterman (Oceanography, 2025)
Given the United Nations’ ambitious goal—endorsed by more than 100 nations, including Canada—of protecting 30% of the world’s marine ecosystems by 2030 (UN, 2023), the need to establish, expand, and track the effectiveness of protected areas is becoming more pressing each year. Effective planning for and monitoring of marine protected areas (MPAs) rely on the availability of quality baseline ecological and oceanographic information. Many of the sites in the Canadian Pacific Ocean best suited for protection, due to the confluence of ecological, cultural, and political significance, are remote. This poses two challenges: (1) there is little baseline information to guide planning, and (2) they are challenging to monitor once established.

Modelling the spread of a novel endosymbiont infection in field populations of an aphid pest - Alex Slavenko; Perran A Ross; Luis Mata; Ary A Hoffmann; Paul A Umina (Ecological Modelling, 2024)

Sustainable seaweed aquaculture and climate change in the North Atlantic: challenges and opportunities - Reina J. Veenhof; Michael T. Burrows; Adam D. Hughes; Kati Michalek; Michael E. Ross; Alex I. Thomson; Jeffrey Fedenko; Michele S. Stanley (Frontiers in Marine Science, 2024)
Seaweed aquaculture is gaining traction globally as a solution to many climate issues. However, seaweeds themselves are also under threat of anthropogenically driven climate change. Here, we summarize climate-related challenges to the seaweed aquaculture industry, with a focus on the developing trade in the North Atlantic. Specifically, we summarize three main challenges: i) abiotic change; ii) extreme events; and iii) disease & herbivory. Abiotic change includes negative effects of ocean warming and acidification, as well as altered seasonality due to ocean warming. This can lower biomass yield and change biochemical composition of the seaweeds. Extreme events can cause considerable damage and loss to seaweed farms, particularly due to marine heatwaves, storms and freshwater inputs. Seaweed diseases have a higher chance of proliferating under environmentally stressful conditions such as ocean warming and decreased salinity. Herbivory causes loss of biomass but is not well researched in relation to seaweed aquaculture in the North Atlantic. Despite challenges, opportunities exist to improve resilience to climate change, summarized in three sections: i) future proof site selection; ii) advances in breeding and microbiome manipulation; and iii) restorative aquaculture. We present a case study where we use predictive modelling to illustrate suitable habitat for seaweed cultivation in the North Atlantic under future ocean warming. Notably, there was a large loss of suitable habitat for cultivating Alaria esculenta and Laminaria digitata . We show how selection and priming and microbe inoculates may be a cost-effective and scalable solution to improve disease- and thermal tolerance. Co-cultivation of seaweeds may increase both yield and biodiversity co-benefits. Finally, we show that aquaculture and restoration can benefit from collaborating on nursery techniques and push for improved legislation.

Influence of genetic and environmental factors on the success of endosymbiont transfers in pest aphids - Xinyue Gu; Perran A. Ross; Qiong Yang; Alex Gill; Paul A. Umina; Ary A. Hoffmann (Environmental Microbiology, 2024)
There is increasing interest in exploring how endosymbionts could be useful in pest control, including in aphids, which can carry a diversity of endosymbionts. Endosymbionts often have a large impact on host traits, and their presence can be self‐sustaining. Identifying useful host‐endosymbiont combinations for pest control is facilitated by the transfer of specific endosymbionts into target species, particularly if the species lacks the endosymbiont. Here, we complete a comprehensive literature review, which included 56 relevant papers on endosymbiont transfer experiments in aphids, to uncover factors that might influence transfer success. We then report on our own microinjection attempts of diverse facultative endosymbionts from a range of donor species into three agriculturally important aphid species as recipients: the green peach aphid ( Myzus persicae ), bird cherry‐oat aphid ( Rhopalosiphum padi ), and Russian wheat aphid ( Diuraphis noxia ). Combining this information, we consider reasons that impact the successful establishment of lines carrying transferred endosymbionts. These include a lack of stability in donors, deleterious effects on host fitness, the absence of plant‐based (versus vertical) transmission, high genetic variation in the endosymbiont, and susceptibility of an infection to environmental factors. Taking these factors into account should help in increasing success rates in future introductions.

Genetic sex determination improves Canadian Atlantic salmon ( Salmo salar ) population assessments - Martha J. Robertson; Sarah J. Lehnert; Nicholas I. Kelly; Lorraine C. Hamilton; Ross A. Jones; Alex L. Levy; Rebecca Poole; Chantelle M. Burke; Steven J. Duffy; Amber Messmer; Ian R. Bradbury (Fisheries Management and Ecology, 2024)
Estimating egg deposition for Atlantic salmon population assessments is made difficult by their lack of sexual dimorphism prior to the autumn spawning season. We quantified the effect of sex misclassification from subjective examination of external morphology on egg deposition estimates in four Atlantic salmon populations across multiple years. Sex classification of Canadian salmon using the genetic sex marker ( sd Y) was accurate (>97%), whereas sex classification based on subjective examination of external morphology was inaccurate, with misclassification rates dependent on sea age, life history, and sampling season. Sex misclassification led to annual egg deposition estimates that ranged from −36% to +56%. We found that sex could not be discriminated based on measures of external morphology.

A diversity of endosymbionts across Australian aphids and their persistence in aphid cultures - Qiong Yang; Alex Gill; Katie L. Robinson; Paul A. Umina; Perran A. Ross; Dongwu Zhan; Courtney Brown; Nicholas Bell; Ashley MacMahon; Ary A. Hoffmann (Environmental Microbiology, 2023)
There is increasing interest in the use of endosymbionts in pest control, which will benefit from the identification of endosymbionts from potential donor species for transfer to pest species. Here, we screened for endosymbionts in 123 Australian aphid samples across 32 species using 16S DNA metabarcoding. We then developed a qPCR method to validate the metabarcoding data set and to monitor endosymbiont persistence in aphid cultures. Pea aphids ( Acyrthosiphon pisum ) were frequently coinfected with Rickettsiella and Serratia , and glasshouse potato aphids ( Aulacorthum solani ) were coinfected with Regiella and Spiroplasma ; other secondary endosymbionts detected in samples occurred by themselves. Hamiltonella , Rickettsia and Wolbachia were restricted to a single aphid species, whereas Regiella was found in multiple species. Rickettsiella , Hamiltonella and Serratia were stably maintained in laboratory cultures, although others were lost rapidly. The overall incidence of secondary endosymbionts in Australian samples tended to be lower than recorded from aphids overseas. These results indicate that aphid endosymbionts probably exhibit different levels of infectivity and vertical transmission efficiency across hosts, which may contribute to natural infection patterns. The rapid loss of some endosymbionts in cultures raises questions about factors that maintain them under field conditions, while endosymbionts that persisted in laboratory culture provide candidates for interspecific transfers.

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Correction to: Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Effects of seawater pCO2 on the skeletal morphology of massive Porites spp. corals - Nicola Allison; Phoebe Ross; Alex Brasier; Nadia Cieminska; Nicolas Lopez Martin; Catherine Cole; Chris Hintz; Ken Hintz; Adrian Finch (Marine Biology, 2022)
Ocean acidification alters the dissolved inorganic carbon chemistry of seawater and can reduce the calcification rates of tropical corals. Here we explore the effect of altering seawater pCO 2 on the skeletal morphology of 4 genotypes of massive Porites spp. which display widely different calcification rates. Increasing seawater pCO 2 causes significant changes in in the skeletal morphology of all Porites spp. studied regardless of whether or not calcification was significantly affected by seawater pCO 2 . Both the median calyx size and the proportion of skeletal surface occupied by the calices decreased significantly at 750 µatm compared to 400 µatm indicating that polyp size shrinks in this genus in response to ocean acidification. The coenosteum, connecting calices, expands to occupy a larger proportion of the coral surface to compensate for this decrease in calyx area. At high seawater pCO 2 the spines deposited at the skeletal surface became more numerous and the trabeculae (vertical skeletal pillars) became significantly thinner in 2 of the 4 genotypes. The effect of high seawater pCO 2 is most pronounced in the fastest growing coral and the regular placement of trabeculae and synapticulae is disturbed in this genotype resulting in a skeleton that is more randomly organised. The study demonstrates that ocean acidification decreases the polyp size and fundamentally alters the architecture of the skeleton in this major reef building species from the Indo-Pacific Ocean.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

The ecological impacts of multiple environmental stressors on coastal biofilm bacteria - Robert M. W. Ferguson; Eoin J. O’Gorman; David J. McElroy; Boyd A. McKew; Ross A. Coleman; Mark C. Emmerson; Alex J. Dumbrell (Global Change Biology, 2021)
Ecological communities are increasingly exposed to multiple interacting stressors. For example, warming directly affects the physiology of organisms, eutrophication stimulates the base of the food web, and harvesting larger organisms for human consumption dampens top‐down control. These stressors often combine in the natural environment with unpredictable results. Bacterial communities in coastal ecosystems underpin marine food webs and provide many important ecosystem services (e.g. nutrient cycling and carbon fixation). Yet, how microbial communities will respond to a changing climate remains uncertain. Thus, we used marine mesocosms to examine the impacts of warming, nutrient enrichment, and altered top‐predator population size structure (common shore crab) on coastal microbial biofilm communities in a crossed experimental design. Warming increased bacterial α‐diversity (18% increase in species richness and 67% increase in evenness), but this was countered by a decrease in α‐diversity with nutrient enrichment (14% and 21% decrease for species richness and evenness, respectively). Thus, we show some effects of these stressors could cancel each other out under climate change scenarios. Warming and top‐predator population size structure both affected bacterial biofilm community composition, with warming increasing the abundance of bacteria capable of increased mineralization of dissolved and particulate organic matter, such as Flavobacteriia, Sphingobacteriia, and Cytophagia. However, the community shifts observed with warming depended on top‐predator population size structure, with Sphingobacteriia increasing with smaller crabs and Cytophagia increasing with larger crabs. These changes could alter the balance between mineralization and carbon sequestration in coastal ecosystems, leading to a positive feedback loop between warming and CO 2 production. Our results highlight the potential for warming to disrupt microbial communities and biogeochemical cycling in coastal ecosystems, and the importance of studying these effects in combination with other environmental stressors.

Climate sensitivity of understory trees differs from overstory trees in temperate mesic forests - Christine R. Rollinson; M. Ross Alexander; Alex W. Dye; David J. P. Moore; Neil Pederson; Valerie Trouet (Ecology, 2021)
The response of understory trees to climate variability is key to understanding current and future forest dynamics. However, analyses of climatic effects on tree growth have primarily focused on the upper canopy, leaving understory dynamics unresolved. We analyzed differences in climate sensitivity based on canopy position of four common tree species ( Acer rubrum , Fagus grandifolia , Quercus rubra , and Tsuga canadensis ) using growth information from 1,084 trees across eight sites in the northeastern United States. Effects of canopy position on climate response varied, but were significant and often nonlinear, for all four species. Compared to overstory trees, understory trees showed stronger reductions in growth at high temperatures and varied shifts in precipitation response. This contradicts the prevailing assumption that climate responses, particularly to temperature, of understory trees are buffered by the overstory. Forest growth trajectories are uncertain in compositionally and structurally complex forests, and future demography and regeneration dynamics may be misinferred if not all canopy levels are represented in future forecasts.

Satellite Image-Based Time Series Observations of Vegetation Response to Hurricane Irma in the Lower Florida Keys - Jan Svejkovsky; Danielle E. Ogurcak; Michael S. Ross; Alex Arkowitz (Estuaries and Coasts, 2020)

Comparing Deep-Sea Larval Dispersal Models: A Cautionary Tale for Ecology and Conservation - Rebecca E. Ross; W. Alex M. Nimmo-Smith; Ricardo Torres; Kerry L. Howell (Frontiers in Marine Science, 2020)

Size–growth asymmetry is not consistently related to productivity across an eastern US temperate forest network - Alex Dye; M. Ross Alexander; Daniel Bishop; Daniel Druckenbrod; Neil Pederson; Amy Hessl (Oecologia, 2019)

A Multidisciplinary Approach for Generating Globally Consistent Data on Mesophotic, Deep-Pelagic, and Bathyal Biological Communities - Lucy Woodall; Dominic Andradi-Brown; Andrew Brierley; Malcolm Clark; Douglas Connelly; Rob Hall; Kerry Howell; Veerle Huvenne; Katrin Linse; Rebecca Ross; Paul Snelgrove; Paris Stefanoudis; et al. (Oceanography, 2018)

Singlicate Ligand Binding Assay Using an Automated Microfluidic System: a Clinical Case Study - Hao Jiang; Alex Kozhich; Jennifer Cummings; Janice Gambardella; Frank Zambito; Craig Titsch; Jonathan Haulenbeek; Kelli Phillips; Ross Fergus; Heather Myler (The AAPS Journal, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Observations of below-ground characteristics of young redwood trees (Sequoia sempervirens) from two sites in New Zealand – implications for erosion control - Christopher J. Phillips; Michael Marden; Suzanne Lambie; Alex Watson; Craig Ross; Scott Fraser (Plant and Soil, 2013)

The effects of recreational sport on VO2peak, VO2 kinetics and submaximal exercise performance in males and females - Brittany A. Edgett; Jonathan E. D. Ross; Alex E. Green; Norah J. MacMillan; Kevin J. Milne; Brendon J. Gurd (European Journal of Applied Physiology, 2013)

Habitat preference and dispersal of the Duke of Burgundy butterfly (Hamearis lucina) on an abandoned chalk quarry in Bedfordshire, UK - Edgar C. Turner; Hanna M. V. Granroth; Henry R. Johnson; Colin B. H. Lucas; Alex M. Thompson; Hannah Froy; Richard N. German; Ross Holdgate (Journal of Insect Conservation, 2009)

Evidence of a significant wind‐driven circulation in Akaroa Harbour. Part 2: Results from the application of a width averaged hydrodynamic numerical model (CE‐QUAL‐W2) - Darlene N. Heuff; Robert H. Spigel; Alex H. Ross (New Zealand Journal of Marine and Freshwater Research, 2005)
Results from the application of the two‐dimensional, laterally‐averaged hydrodynamic model, CE‐QUAL‐W2 to Akaroa Harbour, New Zealand were compared with 3 months of temperature and current data to investigate the connection between significant wind‐driven circulation and vertical mixing. Results indicate that in general, CE‐QUAL‐W2 reproduced realistic values for width‐averaged along‐Harbour current speeds and water column temperature structure. However, during periods of strong winds, the mixed layer depth was predicted to be shallower than observed; c. one‐third as compared to c. one‐half. Simulations of tidally‐driven flow highlighted the restrictions of the two‐dimensionality imposed by the model, though this type of flow was not found to result in appreciable mixing of the water column. Data from an independent field survey supported the validity of the use of CE‐QUAL‐W2 under (at least) light‐to‐moderate sea‐breeze conditions.

Evidence of a significant wind‐driven circulation in Akaroa Harbour. Part 1: Data obtained during the September‐November, 1998 field survey - Darlene N. Heuff; Robert H. Spigel; Alex H. Ross (New Zealand Journal of Marine and Freshwater Research, 2005)
Part 1 (P1) of a two‐part study of Akaroa Harbour, Bank's Peninsula, New Zealand, presents observational evidence of the development of a significant wind‐driven circulation in association with strong northerly and southerly wind events. These are common throughout the year though during the 3‐month field campaign (during the Southern Hemisphere spring of 1998) northerly wind events dominated. This wind‐driven circulation resulted in the weakening of density stratification within the Harbour, mixing the water column to depth over a significant portion of the study area.

Seasonal variation in the reproductive activity and biochemical composition of the Pacific oyster (Crassostrea gigas) from the Marlborough Sounds, New Zealand - Jeffrey S. Ren; Islay D. Marsden; Alex H. Ross; David R. Schiel (New Zealand Journal of Marine and Freshwater Research, 2003)
Reproductive cycles of the Pacific oyster Crassostrea gigas (Thunberg) from the Marlborough Sounds, New Zealand, were followed between June 1998 and January 2000. Histological examination of the gonad confirms an annual cycle with a winter inactive period followed by rapid gonad development and a single short spawning period. The population gonad index correlated with seawater temperature and changes in tissue dry weight, condition index, and biochemical components. In winter, few individuals with early gametogenic stages were present and rapid development of primary oocytes (diam. 11 μm) occurred during spring (September‐November). The developmental rate and the diameter of mature oocytes (37 μm) was similar for the 1998 and 1999 seasons. For a standard 110‐mm‐length oyster, maximal tissue body weight and condition index were recorded in December. Rapid weight loss in January was length dependent and was attributed to spawning. Temperature was the environmental variable which best correlated with the timing of gametogenesis. Food availability (phytoplankton biomass) may have been responsible for inter‐annual variations. The biochemical composition (% glycogen, lipid, protein) of separated gonad and somatic tissues were variable seasonally and annually. Gametogenesis (oocyte diameter) was associated with increased gonad protein and glycogen and a decrease in lipid concentrations. These changes are similar to those in Pacific oyster populations from other parts of the world.